2021
DOI: 10.1136/heartjnl-2020-318139
|View full text |Cite
|
Sign up to set email alerts
|

Implications of cancer prior to and after heart transplantation

Abstract: Cancer and cardiovascular disease share many risk factors. Due to improved survival of patients with cancer, the cohort of cancer survivors with heart failure referred for heart transplantation (HT) is growing. Specific considerations include time interval between cancer treatment and HT, risk for recurrence and risk for de novo malignancy (dnM). dnM is an important cause of post-HT morbidity and mortality, with nearly a third diagnosed with malignancy by 10 years post-HT. Compared with the age-matched general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…1,11 Although a prior history of malignancy is known to predict future development, 2 the risk is higher based on the time in remission prior to transplant. 1,27 This level of detail was not available in the SRTR and was, therefore, not accounted for in our model. Our model also suggested that increasing recipient age at transplant has a strong relationship with posttransplant malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 Although a prior history of malignancy is known to predict future development, 2 the risk is higher based on the time in remission prior to transplant. 1,27 This level of detail was not available in the SRTR and was, therefore, not accounted for in our model. Our model also suggested that increasing recipient age at transplant has a strong relationship with posttransplant malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Improved survival of cancer patients has led to an increase in the cohort of patients with a history of malignancy undergoing HT in recent years [ 45 ]. For these patients, the risk of recurrence or de novo cancer has increased about 2.5–4-times compared with the general population of the same age [ 46 , 47 ].…”
Section: Contraindications To Htmentioning
confidence: 99%
“…Most organ specific malignancies are a contraindication for transplantation, and non-liver solid malignancy is a contraindication for 5 years for liver transplantation. It should be noted that there have been recent suggestions to use a more tailored risk assessment for these patients [123][124][125]. This additional…”
Section: Current Barriers To Implementation Of Palliative Care In Hccmentioning
confidence: 99%
“…It should be noted that there have been recent suggestions to use a more tailored risk assessment for these patients. [115][116][117] This additional therapeutic option often causes significant uncertainty in the clinical prognosis of HCC patients. Since patients are potentially curative but have significant symptom burden, there is poor acceptability of palliative and supportive care intervention due to clinician belief around the utilization of these services while patients are still undergoing "active" treatment.…”
Section: Current Barriers To Implementation Of Palliative Care In Hccmentioning
confidence: 99%